2006
DOI: 10.1002/jsfa.2645
|View full text |Cite
|
Sign up to set email alerts
|

Quality and safety of halawa modified with mushroom

Abstract: Halawa supplemented with 10-120 g mushroom, was evaluated for its acceptability (color, taste, texture, separate oil and overall acceptability by a ten-member panel), protein content (as amino acid content), microbiological safety and quality. Halawa supplemented with both 10 and 20 g mushroom was equally as acceptable as the unsupplemented halawa in most sensory attributes. Results indicated that the low percentage of mushroom in halawa and control samples gave a higher panel score of all organoleptic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 19 publications
6
18
0
Order By: Relevance
“…Moisture content, ash, crude oil, total carbohydrate and protein ranged from 0.66 to 1.25%, 1.36 to 2.16%, 31.16 to 35.99%, 47.67 to 52.10%, and 12.04 to 15.21%, respectively. These values are similar to results of halva fortified with mushroom (Eissa and Zohair ) and Tahin halva (Kotzekidou ). The use of vegetable oil caused chemical composition of halva mixtures was constrained in a narrow range.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Moisture content, ash, crude oil, total carbohydrate and protein ranged from 0.66 to 1.25%, 1.36 to 2.16%, 31.16 to 35.99%, 47.67 to 52.10%, and 12.04 to 15.21%, respectively. These values are similar to results of halva fortified with mushroom (Eissa and Zohair ) and Tahin halva (Kotzekidou ). The use of vegetable oil caused chemical composition of halva mixtures was constrained in a narrow range.…”
Section: Resultssupporting
confidence: 87%
“…Sesame paste is then blended with the syrup, kneaded, molded and packaged (Sengun et al . ; Eissa and Zohair ; Kahraman et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers have determined the emulsion stability of tahin depended on both storage temperature and particle dimension, hence they stated that storage temperature was more effective on emulsion stability than particle dimension. Eissa and Zohair (2006) investigated the changes of some quality characteristics in modified helva with dried mushroom (oyster mushroom, Pleurotus sajor-caju) during storage at 25°C for 6 months. It was found that colour value of a and browning index of helva increased depending on the increasing mushroom concentration (from 10 g/kg to 120 g/kg) in tahin helva.…”
Section: Oil Separationmentioning
confidence: 99%
“…The device was calibrated on a white standard tile ( L* = 98.45, a* = −0.10, b* = −0.13). In this system, L* represents lightness (high values) and darkness (low values), + a* redness, − a* greenness, + b* yellowness, − b* blueness (Eissa & Zohair, ). At each storage time L* , a* , b* parameters of color were measured.…”
Section: Methodsmentioning
confidence: 99%